Child Outcomes for Mothers Facing Trial (COMFT): sharing learning about linking data across sectors of criminal and family justice. - Broadhurst, Karen; Griffiths, Lucy; Humphreys, Leslie (International Journal of Population Data Science, 2025)
Objectives The objectives of the COMFT study (funded by the ESRC) are to generate new knowledge about female defendants who are also involved in the family justice system, and to understand caregiver outcomes for children. This collaborative study aims to assist policy makers as they strive to preserve mother-child relationships, to reduce offending. Methods Administrative records for female defendants appearing in the criminal courts (and prisons data), are linked to records for women appearing in the family courts (public and private law). Criminal court records provide information on offence type and case outcomes. Family court data enables children to be linked to their mothers, and provides children’s legal order outcome information. Records are accessed by a highly experienced, interdisciplinary team (inter-university; family justice and crime specialists) of researchers through the SAIL Databank. Year 1 (2025) comprises examination and documentation of data quality, scope, and dataset build. Year 2 (2026) comprises experimental sub-studies which provide new knowledge about dual system involvement. Results The project team will share learning from Year 1 regarding progress towards the creation of cross-justice datasets. This will include all elements of navigating access and responding to governance requirements, new learning about data quality, scope and linkages, cohort design decisions and outcome definitions. Provisional descriptive results about the populations of mothers and their children will be shared, including demographic information which addresses questions of dual system involvement according to deprivation and ethnicity. Sharing Year 1 results will enable other researchers to understand the opportunities and limitations of linking data across justice systems (England and Wales). The team will also share learning about working with project partners, including mothers with cross-justice lived experience. Conclusions The project has been designed collaboratively with partners: the Ministry of Justice (MoJ), Cafcass and Cafcass Cymru, Birth Companions and COMFT-Together (Mothers with Lived Experience). It builds on the MoJ’s Data First programme and addresses questions that are long overdue about mothers and children at the intersection of criminal justice.